Predictors of changes in incisor inclination during orthodontic levelling and alignment with fixed appliances: a retrospective cross-sectional study - Camilla Sahm; Christian Kirschneck; Peter Proff; Eva Paddenberg-Schubert (Head & Face Medicine)
Abstract Introduction Labial tipping of the incisors, observed during levelling and alignment in orthodontic treatment with multibracket-appliances, can be an undesired side effect due to its association with relapse and attachment loss in excessive cases. Therefore, its pre-treatment prediction is useful to individualise treatment plans correspondingly. This retrospective cross-sectional study aimed to establish regression equations predicting incisors’ inclination changes during levelling and alignment with fixed appliances in orthodontic patients using lateral cephalograms. Potential predictors analysed included clinical and cephalometric parameters. Methods Patients of any age and malocclusion were screened for inclusion, and the upper and lower arches were evaluated separately. Lateral cephalograms taken at T0 and T1, initial plaster models and patient records were analysed. Multiple linear regression models were performed to establish regression equations, identifying predictors of incisors’ inclination changes. Results The final study population was comprised of 216 female (n = 123, 56.9%) and male (n = 93, 43.1%) orthodontic patients (147 upper, 151 lower arches) aged between 9.3 and 30.0 years with a mean age of 13.1 years ± 2.1. Interrater- and intrarater-reliability showed perfect measurement concordance for all cephalometric parameters and moderate to perfect concordance for categorical variables. Sagittal changes of the upper incisors’ inclination (Δ1-NL) were dependent on initial anterior crowding, initial incisor inclination and intermaxillary elastics (corrected R2 = 0.375, n = 147). In the lower jaw, incisors’ proclination (Δ1-ML) was predicted by anterior crowding, incisor inclination, growth pattern, skeletal class and bracket type (corrected R2 = 0.468, n = 151). Changes in the interincisal angle (Δ1–1) were significantly predicted by mandibular anterior crowding and initial inclination of the upper and lower incisors (corrected R2 = 0.440, n = 82). Conclusions Regression equations with specific clinical and cephalometric parameters are suitable to predict the degree of incisors’ inclination changes during alignment with fixed appliances. The amount of anterior crowding and the initial incisors’ inclination of the respective jaw were relevant in all three formulas. Using the predictors may reduce undesired excessive inclination changes and help in individualised treatment planning. However, as more than 50% of the variance are explained by other factors, they act as an adjunctive method to the remaining procedures of treatment planning.